COVID-19 preventive practices, psychological distress, and reported barriers to healthcare access during the pandemic among adult community members in sub-Saharan Africa: a phone survey - Assefa, Nega; Abdullahi, Yasir Y.; Hemler, Elena C.; Lankoande, Bruno; Madzorera, Isabel; Wang, Dongqing; Ismail, Abbas; Chukwu, Angela; Workneh, Firehiwot; Mapendo, Frank; Millogo, Ourohiré; Abubakari, Sulemana Watara; et al. (The American journal of tropical medicine and hygiene, 2023)
ABSTRACT. The COVID-19 pandemic has had serious negative health and economic impacts in sub-Saharan Africa. Continuous monitoring of these impacts is crucial to formulate interventions to minimize the consequences of COVID-19. This study surveyed 2,829 adults in urban and rural sites among five sub-Saharan African countries: Burkina Faso, Ethiopia, Nigeria, Tanzania, and Ghana. Participants completed a mobile phone survey that assessed self-reported sociodemographics, COVID-19 preventive practices, psychological distress, and barriers to healthcare access. A modified Poisson regression model was used to estimate adjusted prevalence ratios (aPRs) and 95% CIs to investigate potential factors related to psychological distress and barriers to reduced healthcare access. At least 15.6% of adults reported experiencing any psychological distress in the previous 2 weeks, and 10.5% reported that at least one essential healthcare service was difficult to access 2 years into the pandemic. The majority of participants reported using several COVID-19 preventive methods, with varying proportions across the sites. Participants in the urban site of Ouagadougou, Burkina Faso (aPR: 2.29; 95% CI: 1.74-3.03) and in the rural site of Kintampo, Ghana (aPR: 1.68; 95% CI: 1.21-2.34) had a higher likelihood of experiencing any psychological distress compared with those in the rural area of Nouna, Burkina Faso. Loss of employment due to COVID-19 (aPR: 1.77; 95% CI: 1.47-2.11) was also associated with an increased prevalence of psychological distress. The number of children under 5 years in the household (aPR: 1.23; 95% CI: 1.14-1.33) and participant self-reported psychological distress (aPR: 1.83; 95% CI: 1.48-2.27) were associated with an increased prevalence of reporting barriers to accessing health services, whereas wage employment (aPR: 0.67; 95% CI: 0.49-0.90) was associated with decreased prevalence of reporting barriers to accessing health services. Overall, we found a high prevalence of psychological distress and interruptions in access to healthcare services 2 years into the pandemic across five sub-Saharan African countries. Increased effort and attention should be given to addressing the negative impacts of COVID-19 on psychological distress. An equitable and collaborative approach to new and existing preventive measures for COVID-19 is crucial to limit the consequences of COVID-19 on the health of adults in sub-Saharan Africa.
Online veröffentlicht: 12 Dec 2022
Gesehen am 21.04.2023